Neoadjuvant systemic therapy in breast cancer: Challenges and uncertainties. (March 2017) - Van de Wiel, Mick; Dockx, Yanina; Van den Wyngaert, Tim; Stroobants, Sigrid; Tjalma, Wiebren A.A.; Huizing, Manon T.
Abstract: The management of locally advanced breast cancer (LABC) remains a major clinical issue, despite progress achieved in diagnosis and therapy. Preoperative or neoadjuvant therapy has gained interest since breast cancer has been regarded as a systemic disease. Comparing adjuvant versus neoadjuvant treatment, the neoadjuvant approach offers the advantage of downstaging the disease and testing the efficacy of therapy administered to patients. A large number of clinical trials have attempted to define the optimal neoadjuvant treatment, but little attention has been paid to the sequence of chemotherapy. Moreover, the integration of antibodies against Human Epidermal Receptor-2 (HER-2) and other biological therapies that may improve the long-term control of breast cancer patients, have a special clinical interest. In this review, we will discuss these topics attempting to answer the questions why, when and which regimen to use for patients with LABC. Especially, the introduction of the platina derivatives in neoadjuvant trials with their exceptional high pathological complete response rates are challenging to rethink the optimal treatment options in early and locally advanced breast cancer.